One subgenome to rule them all: underlying mechanisms of subgenome dominance. (April 2020) - Alger, Elizabeth I; Edger, Patrick P
Highlights: A single subgenome in allopolyploids may contribute to the majority of the phenotype. Methylation of transposons near genes is associated with subgenome dominance. Genetic incompatibility among subgenomes also causes observed dominance patterns. Environment may also influence subgenome dominance patterns. Abstract : Allopolyploids, which are formed from the hybridization of two or more diploid progenitor species, often experience subgenome dominance, where one of the parental genomes (subgenomes) has higher levels of gene expression and ultimately greater gene retention compared to the other subgenomes. Low transposable element (TE) abundance near genes has been associated with the dominant subgenome in several allopolyploids, but TEs are unlikely to be the only causal factor responsible for subgenome expression dominance. In this review, we will examine the role of TEs in subgenome dominance as well as discuss how genetic incompatibilities among subgenomes likely contributes to the rapid emergence of subgenome dominance. Lastly, we highlight several burning questions about subgenome dominance that remain largely unanswered.